Systemic prednisone administration selectively alters granulocyte subsets in nasal polyps from aspirin‐exacerbated respiratory disease and chronic rhinosinusitis patients. Issue 11 (19th September 2013) - Edward, Justin A.; Sanyal, Mrinmoy; Ramakrishnan, Vijay R.; Le, Wei; Nguyen, Alan L.; Kingdom, Todd T.; Hwang, Peter H.; Nayak, Jayakar V.
<x xml:space="preserve">Abstract</x> Background Nasal polyps (NPs) are hallmark inflammatory lesions of sinusitis. Despite the spectrum of NP conditions, cellular differences between NPs from patients with chronic rhinosinusitis with NPs (CRSwNP) and aspirin‐exacerbated respiratory disease (AERD) are poorly understood. NPs are associated with abundant eosinophils; the contributions of neutrophil and basophil granulocytes are less defined. We therefore sought to assess granulocyte subpopulations, and differential effects following prednisone pretreatment, within NPs of CRSwNP and AERD patients. Methods NPs, adjacent ethmoid sinus tissue, and peripheral blood mononuclear cells (PBMCs) were obtained from patients undergoing endoscopic sinus surgery. Samples from 5 cohorts: CRSwNP ± prednisone (n = 6 each), AERD ± prednisone (n = 6 each), and controls (n = 9), were analyzed by high‐dimensional flow cytometry to gate granulocyte populations. Specimens were also assessed using immunohistochemistry (IHC) staining. Results Systemic prednisone administration was associated with a lower frequency of eosinophils (p < 0.0001, n = 6) in NPs in both CRSwNP and AERD patients, whereas a decrease in neutrophils (p = 0.0070, n = 6) in NPs was only observed in CRSwNP patients after prednisone treatment. In contrast, steroids do not alter basophil proportions (p = 0.48, n = 6) within NPs from either group. No significant shift in granulocyte subsets after steroid treatment was identified in the adjacent ethmoid mucosa or PBMCs from the same patients. Immunohistochemistry (IHC) staining supported these findings. Conclusion Granulocyte subpopulations are focally affected within NPs by systemic steroid exposure, without notable granulocyte alterations in the surrounding regional tissues. These data provide direct insights into the cellular effects of routine prednisone exposure in CRS patients, and highlight a unique microenvironment present within NP lesions.